Membangun Kemampuan Moderasi Beragama dalam Pendidikan untuk Mencapai Perdamaian dan Persatuan: Literature Review - Shoffiyah Salsabil (Yayasan Nurul Musthafa, 2025)
Religious moderation is a middle-ground, balanced, and moderate attitude aimed at fostering peace amidst differences. It serves as a preventive measure against oppression resulting from society’s inability to comprehend diversity. In this context, education becomes a crucial sector for adopting religious moderation to build a harmonious and respectful society. This article aims to identify the competencies developed when individuals adopt a moderate stance. This study employs a systematic literature review (SLR) methodology following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. The search utilized two keywords: